Drug Prevention Outreach: Enhancing Youth Knowledge and Awareness in Ureng Country, Maluku Tengah, Indonesia - Fransina S Latumahina; Anshari Betekeneng; Dandi Alvian Hakim; Arman Wally; Ari Fisal Waelissa (Universitas Muhammadiyah Sidoarjo, 2023)
The dangers and detrimental effects of drugs on the lives and health of addicts and their families have become increasingly concerning. This study aimed to address the lack of understanding about narcotics among the youth in Ureng Country, which consists mostly of vulnerable individuals susceptible to drug contamination. The research was conducted through a community engagement initiative called the